CULTIVATING CIVIC CHARACTER THROUGH CO-CURRICULAR PROGRAMS CONTAINING LOCAL WISDOM - Amelia Sholihah; Sudrajat (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the influence of local wisdom-based co-curricular programs on the formation of student citizenship character at SMP Negeri 16 Cimahi. The co-curricular program implemented takes the theme "Bhinneka Tunggal Ika: Different Colors but One Feeling of Unity in Diversity" with cultural performance activities, traditional games, and collaborative projects oriented towards strengthening social values. The study used a mixed methods approach with a sequential explanatory design, involving 100 students as quantitative respondents and 9 qualitative informants. The research instruments were a Likert scale questionnaire, observation, in-depth interviews, and document analysis. The results of the quantitative analysis showed that students' citizenship character was in the high category (M = 4.19) and there was a strong positive relationship between the co-curricular program and citizenship character (r = 0.71) with a contribution of 39% (R² = 0.39). Qualitative findings confirm an increase in social responsibility, caring, empathy, and respect for differences through the internalization of the values ​​of silih asih-silih asah-silih asuh and tepa selira. This study concludes that local wisdom-based co-curricular activities are effective as a strategy for developing civic character, but students' social participation still needs to be strengthened through community service-based activities.